Family in cinema: the construction of discourses in contemporaries Hollywood movies - Coelho, Paloma (2014)
This article aims to reflect on the construction of discourses on the family in films of Hollywood produced and/or displayed in the last two decades, based on the results of my master’s thesis, entitled “Look closer: the construction of speeches about family in the contemporary Hollywood films”. Starting from the idea that a film is a product of his time, that is, they do not relieve from the visions and values of the time it was produced, it seeks to understand how the Hollywood cinema has approached the family configurations before the significant changes that have occurred in the design of family in the last few decades.